PERAMALAN SUHU UDARA DAN DAMPAKNYA TERHADAP KONSUMSI ENERGI LISTRIK DI KALIMANTAN TIMUR - Susanti, Lisa; Hasanah, Primadina; Winarni, Winarni (PATTIMURA UNIVERSITY, 2020)
The increase in air temperature due to climate change and global warming has become a major concern for policy makers, one of which is the government of East Kalimantan. Electric energy consumption has a close relationship with economic development in East Kalimantan. So it is necessary to forecast the temperature of air in order to predict the consumption of electrical energy in the future. The purpose of this study was to determine the forecasting of air temperatures in East Kalimantan, namely the cities of Balikpapan, Samarinda and Berau and to determine the relationship between air temperature and electricity consumption in East Kalimantan. In this study, the method used is the ARIMA (Autoregressive Integrated Moving Average) and multiple linear regression methods. The results of the analysis using the ARIMA method obtained the best models for the cities of Balikpapan, Samarinda and Berau respectively, namely ARIMA(1,1,1), ARIMA(1,1,1) and ARIMA(3,1,0). Based on the results of multiple linear regression obtained R-square value of 39%, which mean that the influence of air temperature on the consumption of electrical energy is 39%. From the results of the t test and F test, it is known that air temperature has a significant effect on the increase in electricity consumption in East Kalimantan